2021
DOI: 10.1186/s12917-021-02922-w
|View full text |Cite
|
Sign up to set email alerts
|

Inter and intraspecies comparison of the level of selected bacterial phyla in in cattle and sheep based on feces

Abstract: Background The microbiome of the digestive tract of ruminants contains microbial ecosystem that is affected by both environmental and genetic factors. The subject of this study concerns the influence of selected genetic factors, such as species of animals and “host” individual differences on the digestive tract microbiome composition. The results show the core microbiological composition (Firmicutes and Bacteroidetes) of ruminants digestive tract (based on feces) depending on breed and “host”. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…These animals have specific gut microbial taxa as they are dependent on these bacteria to extract energy and nutrients from food (54) , besides having specialized anatomical and physiological adaptations to the cellulolytic fermentation of low nutrition -high fiber vegetal material (55) . The presence of other bacterial genera reported in this study could be the result of environmental and genetic factors, age, breed, diet, phylogeny, among others (56,57,58) . Recently (56,59,60) , was demonstrated that herbivorous animals have the most diverse microbiota since they depend on microbial metabolic pathways to maximize energy and nutrient extraction from feeding (61) .…”
Section: Resultsmentioning
confidence: 63%
“…These animals have specific gut microbial taxa as they are dependent on these bacteria to extract energy and nutrients from food (54) , besides having specialized anatomical and physiological adaptations to the cellulolytic fermentation of low nutrition -high fiber vegetal material (55) . The presence of other bacterial genera reported in this study could be the result of environmental and genetic factors, age, breed, diet, phylogeny, among others (56,57,58) . Recently (56,59,60) , was demonstrated that herbivorous animals have the most diverse microbiota since they depend on microbial metabolic pathways to maximize energy and nutrient extraction from feeding (61) .…”
Section: Resultsmentioning
confidence: 63%
“…In a separate study, certain members of the Firmicutes phylum, such as Christensenellaceae and Lachnospiraceae, were reported to have potentially higher abundance when sampling liquid-based fluid via stomach sampling [ 41 ]. Furthermore, numerous factors, including geographical location and diet, have been identified as influential contributors to the microbial diversity and quantity within the digestive tract [ 42 ]. Under high-concentrate feeding conditions, Firmicutes accounted for over 70% of the detected microbes.…”
Section: Discussionmentioning
confidence: 99%
“…The sum of Firmicutes and Bacteroidota was more than 95.11% in both fine wool sheep in this experiment. Firmicutes contain many fiber-decomposing bacteria, which are related to fiber degradation and fat deposition in the rumen [42,43]. Bacteroidota has the ability to degrade plant polysaccharides and is mainly involved in the degradation process of starch [44,45], and they help digest and absorb carbohydrates.…”
Section: Differences In the Rumen Flora Structure Of Tianhua Mutton S...mentioning
confidence: 99%